Gamification as Online Teaching Strategy During COVID-19: A Mini-Review - Nieto-Escamez, Francisco Antonio; Roldán-Tapia, María Dolores (Frontiers in Psychology, 2021)
The ongoing pandemic caused by the coronavirus disease (COVID-19) have enforced a shutdown of educative institutions of all levels, including high-school and university students, and has forced educators and institutions to adapt teaching strategies in a hasty way. This work reviews the use of gamification-based teaching during the pandemic lockdown through a search in Scopus, PsycInfo, ERIC and Semantic Scholar databases. A total of eleven papers from Chemistry, Business, Computer Science, Biology and Medical areas have been identified and included in the present work. All of them analyzed the use of gamification strategies during COVID-19 pandemic and assessed student’s learning and motivation outcomes. In general, students reported that gamification was innovative, engaging and an efficient strategy to deliver curricula material, moreover it was perceived as fun activity. Some students reported that gamified videoconferences aided to connect with their classmates during isolation time providing effective social support. However, some students reported a bad physical or psychological condition, as consequence of the confinement, and did not get involved in the activity. Some weaknesses of the reviewed studies are the small sample size and its homogeneity, which makes difficult to generalize their results to other scenarios and academic areas. Furthermore, although there is a feeling of learning during the activity, this result is mainly based on subjective perceptions, and any of the studies demonstrated that superior learning was achieved in comparison to traditional teaching strategies. Nevertheless, gamification can be implemented together with traditional lectures and can be a valuable instrument during post-COVID times.